Acute lung injury secondary to e-cigarettes or vaping. Issue 2 (2nd April 2020) - Freathy, Sarah; Kondapalli, Nitin; Patlolla, Srikant; Mora, Adan; Trimmer, Clayton
Abstract: As of October 2019, 1299 cases of "e-cigarette, or vaping, product use associated lung injury" (EVALI) have been reported in the USA, with 26 deaths. Multiple patterns of lung injury have been reported, including lipoid pneumonia, organizing pneumonia, and acute eosinophilic pneumonia, with radiographic findings including diffuse pulmonary infiltrates. We report a case of lipoid pneumonia secondary to EVALI. Physicians should be alert to recognizing these patterns of lung injury, as well as emphasizing to patients the importance of e-cigarette cessation.